Knowledge, attitude and practice of food utensils hygiene amongst food handlers in Kuala Pilah, Negeri Sembilan, Malaysia - Siti Nurul Ain Saipullizan,; Sahilah Abd. Mutalib,; Razalee Sedek, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study aimed to evaluate the level of knowledge, attitude and practice (KAP) amongst food handlers in food utensils hygiene and presence of bacterial contamination on food utensils. There were two approaches used in this study. In the first approach, 134 of food handlers from 75 food premises were interviewed via questionnaires to assess their knowledge, attitude and practice. In the second approach, the presence of Staphylococcus aureus, Escherichia coli and total coliform of 225 utensils (knives (75), chopping boards (75) and dish plates (75)) was examined. The result showed that the food handlers had sufficient level of knowledge (80.5%), attitude (87.4%) and practice (90.1%). Highest contamination was found on the chopping boards for the presence of S. aureus (82.8%), E. coli (9.7%) and total coliform (73.9%). Logistic regression analysis showed that knowledge contributes to the presence of E. coli on the dish plates; and total coliform on the knives. Thus, ongoing training that focused on food utensils hygiene must be emphasized to improve knowledge, attitude and practice amongst the food handlers.